Transformational leadership and employee voice for product and process innovation in SMEs - Muhammad Athar Rasheed; Khuram Shahzad; Sajid Nadeem (Innovation & Management Review, 2021)
Purpose This study aims to investigate the impact of transformational leadership on the innovation of small and medium enterprises (SMEs) through employee voice behaviors. Drawing from the upper echelon theory, it is hypothesized that employee voice is the mediating mechanism through which transformational leadership affects the process and product innovation in SMEs. Design/methodology/approach Data was collected from 169 SMEs of Pakistan through an online self-administered questionnaire. The proposed hypotheses were tested using partial least squares structural equation modeling (PLS-SEM). Findings Findings confirm that transformational leadership positively affects both process and product innovation in SMEs and employee voice behavior mediates between these relationships. Originality/value This research contributes to both theoretical and practical domains by providing evidence that encouraging employees to raise their voice positively impacts product and process innovation and transformational leadership is a potential organizational factor to shape employee voice and process and product innovation. To the best knowledge, this is the first study that investigates the mediating role of employee voice between transformational leadership and process and product innovation in SMEs and developing country's context.
Keywords: 650; Employee voice; Pakistan; Process innovation; Product innovation; Small and medium enterprises (SMEs); Transformational leadership